Online degrees – academic dishonesty and misconduct, why is happening? - Cerimagic, Sabina (IJRDO - Journal of Social Science and Humanities Research, 2016)
In recent years, an increasing number of universities have offered online degrees. Along with this new method of completing degrees comes new forms of academic dishonesty and misconduct. Academic dishonesty and misconduct among students is not a new phenomenon. In 1990, the American Council on Higher Education reported that cheating at was on the rise at universities in the United States (U.S). Following this, researchers started to more intensely investigate the issue of cheating (Kerkvliet, 1994). In recent years, there has been a great deal of research in the area of academic dishonesty (Brimble and Stevenson-Clarke, 2006; Wilkinson, 2009; Stack, 2015). However, much of the research that has been conducted on academic dishonesty and misconduct has almost exclusively focused on the United States (US). This paper contributes to the limited research literature on online programs and online exams and academic dishonesty and misconduct at Australian universities by taking a closer look at what academic dishonesty and misconduct is, how it is happening and how it may be minimised. It is important that these questions be understood because, as found by Smyth et al. (2009), students who cheat at university are more likely to become professionals who in the future will engage in illegal, unethical or immoral behaviours in the workplace.